1973
DOI: 10.1007/bf01474719
|View full text |Cite
|
Sign up to set email alerts
|

Induced hypothermia in peripheral nerve: Electron microscopic and electrophysiological observations

Abstract: SummaryLocalized cooling of the cat sciatic nerve was achieved by application of a thermoelectric device to the exposed nerve at mid-thigh. The temperature of the nerve was maintained at 5°C for z h. Before, during, and after cooling, the response of the nerve to electrical stimulation was monitored, and compared with responses obtained in normothermic control preparations. In all cases, dropping the temperature of the nerve to 5°C resulted in total nerve block, and in all cases, function was restored when coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 49 publications
(7 reference statements)
1
13
0
Order By: Relevance
“…The present values are in bility of nerve fibres in the Trembler close agreement with those of Byck et al (1972) conduct rapid trains of impulses is of and Basbaum (1973) who reported values of 5.3°C cal importance since high frequency disand 5.0°C respectively in their studies on cat cur in normal sensory nerves in animals saphenous and sciatic nerves. I McIntyre, 1960a,b) and man (Hensel The mechanism of cold block was considered by an, 1960).…”
Section: Discussionsupporting
confidence: 86%
“…The present values are in bility of nerve fibres in the Trembler close agreement with those of Byck et al (1972) conduct rapid trains of impulses is of and Basbaum (1973) who reported values of 5.3°C cal importance since high frequency disand 5.0°C respectively in their studies on cat cur in normal sensory nerves in animals saphenous and sciatic nerves. I McIntyre, 1960a,b) and man (Hensel The mechanism of cold block was considered by an, 1960).…”
Section: Discussionsupporting
confidence: 86%
“…This can lead to dysfunction that is equivalent to peripheral paralysis and can, again, result in drowning owing to the inability to keep the airway clear of the water (Clarke et al . ; Basbaum, ; Golden & Tipton, ; Fig. ).…”
Section: Introduction: Historymentioning
confidence: 96%
“…The axon was visualized by the expression of green fluorescent protein (GFP) after transfection of the neuron with a plasmid expressing GFP. Both increases and decreases in temperature have been shown to cause axonal damage, as in the case of hyperthermia or hypothermia [3234]. At the beginning of imaging, the heating stage of the live-cell culture chamber was switched off to gradually reduce the temperature of the neuronal culture from 37 to 22.6°C (room temperature; fig.…”
Section: Resultsmentioning
confidence: 99%